2001
DOI: 10.1046/j.1471-4159.2001.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular resistance to Evans blue toxicity involves an up‐regulation of a phosphate transporter implicated in vesicular glutamate storage

Abstract: It has recently been suggested that the brain-speci®c Na 1 -dependent phosphate inorganic co-transporter (BNPI) is able to support glutamate transport and storage in synaptic vesicles. A procedure for measuring the vesicular pool of glutamate is described and was used to select cell lines according to their glutamate storage capacity. Two cell lines were selected: C6BU-1, with a large intracellular glutamate storage capacity, and NG108-15, devoid of it. Their contents in BNPI mRNA were compared by RT-PCR. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…After recurrent seizure on‐set, VGLUT‐1 immunoreactivity was enhanced in the molecular layer of the dentate gyrus versus controls, although VGAT immunoreactivity recovered to the control level. With respect to previous studies that demonstrated that vesicular transporter expressions can reflect the amount of neurotransmitter release (Daniels et al,2004; Israel et al,2001; Leslie et al,2001; Pawlu et al,2004; Pothos et al,2000), our anatomical data are inconsistent with our electrophysiological findings. However, it is noteworthy that astrocytes can change electrophysiological properties in a synaptic transmission independent manner (McKenna et al,1996; Sonnewald et al,1993; Westergard et al,1995).…”
Section: Discussioncontrasting
confidence: 99%
“…After recurrent seizure on‐set, VGLUT‐1 immunoreactivity was enhanced in the molecular layer of the dentate gyrus versus controls, although VGAT immunoreactivity recovered to the control level. With respect to previous studies that demonstrated that vesicular transporter expressions can reflect the amount of neurotransmitter release (Daniels et al,2004; Israel et al,2001; Leslie et al,2001; Pawlu et al,2004; Pothos et al,2000), our anatomical data are inconsistent with our electrophysiological findings. However, it is noteworthy that astrocytes can change electrophysiological properties in a synaptic transmission independent manner (McKenna et al,1996; Sonnewald et al,1993; Westergard et al,1995).…”
Section: Discussioncontrasting
confidence: 99%
“…EB is commonly used to monitor changes in blood volume and extravasation (Roseth et al, 1995). EB exhibits cytotoxicity on cultured neurons; however, this effect becomes significant only after prolonged EB exposure (Israel et al, 2001). EB was shown to block AMPA-kainate receptors at concentrations approximately two orders of magnitude higher (ϳ10 M IC 50 ) than that for VGLUT3 (Schurmann et al, 1997), whereas its modulatory action on GABA receptors was not reported.…”
Section: Action Of Vglut Inhibitorsmentioning
confidence: 99%
“…Vesicular glutamate transporter is directly involved in insulin secretion from pancreatic β cells, as inhibitors of vesicular glutamate transport suppress the glutamate-evoked insulin exocytosis 5 . Moreover, high glucose concentration increases the cellular glutamate level in rat insulinoma INS-1 cells and this increase can be abolished by carbonyl cyanide ptrifluoromethoxyphenlhydrazone, an inhibitor of vesicular glutamate transporter 19 . These previous studies suggested a potential regulatory role of VGLUTs in glucose-induced insulin secretion of β cell.…”
Section: Introductionmentioning
confidence: 98%